Age-Based Disparities in Metastatic Melanoma Patients Treated in the Immune Checkpoint Inhibitors (ICI) Versus Non-ICI Era: A Population-Based Study - Safi, Mohammed; Al-Azab, Mahmoud; Jin, Chenxing; Trapani, Dario; Baldi, Salem; Adlat, Salah; Wang, Aman; Ahmad, Bashir; Al-madani, Hamza; Shan, Xiu; Liu, Jiwei (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized metastatic melanoma treatment, but our knowledge of ICI activity across age groups is insufficient. Patients in different age groups with advanced melanoma were selected based on the ICI approval time in this study. Patients with melanoma were identified in the Surveillance, Epidemiology, and End Result (SEER) database program 2004–2016. The results showed that 4,040 patients had advanced melanoma before the advent of ICI (referred to as the “non-ICI era”), whereas there were 6,188 cases after ICI approval (referred to as the “ICI era”). In all age groups, the cases were dominated by men. The differences between the first (20–59 years) and second (60–74 years) age groups in both eras were significant in terms of surgery performance and holding of insurance policies (p = 0.05). The first and second groups (20–59 and 60–70 years old, respectively) showed no difference in survival (median = 8 months) during the non-ICI era, but the difference was evident in the first, second, and third age groups in the ICI era, with the younger group (20–59 years) having significantly better survival (median = 18, 14, and 10 months, respectively, p = 0.0001). Multivariate analysis of the first group (the youngest) in the ICI era revealed that surgery was significantly associated with an increase in survival among patients compared with those who did not undergo surgery (p < 0.0001). Furthermore, having an insurance policy among all age groups in the ICI era was associated with favorable survival in the first (20–59 years) and second (60–74 years) age groups (p = 0.0001), while there were no survival differences in the older ICI group (>74 years). Although there were differences in survival between the ICI era and the non-ICI era, these results demonstrate that ICI positively affected the survival of younger patients with advanced melanoma (first age group) than it had beneficial effects on older patients. Moreover, having had cancer surgery and holding an insurance policy were positive predictors for patient survival. This study emphasizes that adequate clinical and preclinical studies are important to enhance ICI outcomes across age groups.